Why Does Education Reduce Crime? - Bell, Brian; Costa, Rui; Machin, Stephen (Journal of Political Economy, 2022)
We provide a unifying empirical framework to study why crime reductions occurred due to a sequence of state-level dropout age reforms enacted between 1980 and 2010 in the United States. Because the reforms changed the shape of crime-age profiles, they generate both a short-term incapacitation effect and a more sustained crime-reducing effect. In contrast to previous research looking at earlier US education reforms, we find that reform-induced crime reduction does not arise primarily from education improvements. Decomposing short- and long-run effects, the observed longer-run effect for the post-1980 education reforms is primarily attributed to dynamic incapacitation.